2023
DOI: 10.1021/acs.jpcc.3c02043
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Current Rectification Induced by Charge Polarity in Janus Graphene Channels

Abstract: Ionic current rectification (ICR) in nanofluidic diodes is determined by a combination of channel geometry and surface charge, where most of the previous works have focused on charged asymmetric channels. In this work, through a series of molecular dynamics simulations, we find a surprising ICR phenomenon in a Janus graphene channel, whose geometry is symmetric, while the surface charge is asymmetric by tuning the ratio of cationic and anionic surface modification. A key observation is that when the electric f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…The number distributions of ions along the z -axis for the six systems are presented in Figure . The results show that the ions distribute mostly in the antielectrical region, similar to the case in electric fields, i.e., Na + is in the COO – -functionalized region and Cl – is in the NH 3 + -functionalized region. Furthermore, the ion distribution peaks locate at the position of residue functionalization, originating from localized ion retention induced by a robust electrostatic interaction, which forms a solid electrical double layer (EDL).…”
Section: Resultsmentioning
confidence: 56%
“…The number distributions of ions along the z -axis for the six systems are presented in Figure . The results show that the ions distribute mostly in the antielectrical region, similar to the case in electric fields, i.e., Na + is in the COO – -functionalized region and Cl – is in the NH 3 + -functionalized region. Furthermore, the ion distribution peaks locate at the position of residue functionalization, originating from localized ion retention induced by a robust electrostatic interaction, which forms a solid electrical double layer (EDL).…”
Section: Resultsmentioning
confidence: 56%
“…As seen in Figure , we construct bipolar Janus GO channels by attaching negatively (COO – ) and positively (NH 3 + ) charged residues onto the inner surface of the graphene channel, resembling the carboxylation and amination of GO. , Experimentally, the charge proportion of Janus channels is determined by measuring the etching depth via modulation of the functionalization time . Previous work has demonstrated that the Janus GO channels with a 1:1 ratio of positive to negative residues have the best rectification performance, and therefore, we focus on this proportion for the present work. The absolute density of surface charge in all investigated channels is fixed at 1.0 e/nm 2 , similar to previous experimental work. , The entire simulation system is shown in Figure S1 of the Supporting Information, where the Janus GO channel is embedded between two graphene sheets in an ionic solution.…”
Section: Model and Simulation Methodsmentioning
confidence: 99%
“…36,37 Experimentally, the charge proportion of Janus channels is determined by measuring the etching depth via modulation of the functionalization time. 38 Previous work has demonstrated that the Janus GO channels with a 1:1 ratio of positive to negative residues have the best rectification performance, 15 and therefore, we focus on this proportion for the present work. The absolute density of surface charge in all investigated channels is fixed at 1.0 e/nm 2 , similar to previous experimental work.…”
Section: ■ Model and Simulation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the latter simulations examined the impact of surface charge in bipolar cylindrical pores on the overall membrane’s performance, with a special emphasis on the relevance of electrokinetic phenomena . A different, recent approach relied on molecular dynamics (MD) simulations to study the ICR in Janus graphene channels . That report considered highly confined geometries with 1–2 nm pore heights and an asymmetric surface charge.…”
Section: Introductionmentioning
confidence: 99%